A comparative study: moral and legal implications of homosexuality and same-sex marriage / Siti Nurzafirah Mohd Padzil, Nur Qistina Suhardi. - Mohd Padzil, Siti Nurzafirah; Suhardi, Nur Qistina (2008)
This research paper is primarily concerned with law and morality in Malaysia. We will discuss on different forms of morality in respect of the matters of the homosexuality and the gay marriages. The position from the Islamic perspective on the different issues relating issues is discussed and at the same time, it is compared with the ever changing public attitude on the issues on the acceptable standards of public morality. Therefore, this research will discuss specifically on laws and morals relating to the homosexuality and gay marriages and to show its relationship with the question of morality and the effect of the standards of law and morality on the subject matter. At the end of this research, we will able to see a different perspective in the law and the influence of the morality on the law and its relationship with society as a whole.